Managing Temper Tantrums in Autistic Middle School Students: A Case Study of Environmental Interventions and Empathetic Approaches in Inclusive Education Settings - Nurhidaya, Nurhidaya; Purwanta, Edi (Papanda Publisher, 2025)
Temper tantrums represent significant behavioral challenges for autistic students in inclusive educational settings, yet comprehensive understanding of their patterns, triggers, and effective management strategies remains limited, particularly during the critical middle school period when academic and social demands intensify. This qualitative case study employed intensive observation and in-depth interviews to examine temper tantrum patterns in an autistic middle school student (FT) within an inclusive classroom setting at SMP Negeri 1 Sangatta Utara over three months. Data were collected through structured interviews with teachers and peers, behavioral observations, and document analysis, with triangulation ensuring data validity. The study identified a three-phase tantrum pattern: pre-crisis indicators (blank staring, table hitting), crisis manifestation (screaming, object throwing, self-injury), and post-crisis withdrawal. Primary triggers included sensory overstimulation from classroom noise, social misunderstandings, and academic pressure. Tantrum frequency and intensity decreased significantly from first to second semester following implementation of empathetic, non-confrontational interventions including environmental modifications, preventive communication, and role-assignment strategies. The behaviors created multi-dimensional impacts affecting classroom dynamics, peer anxiety, and instructional quality. Systematic environmental accommodations combined with empathetic intervention strategies can substantially reduce tantrum frequency and intensity in autistic middle school students. Success requires understanding tantrums as communication attempts reflecting neurological differences rather than behavioral problems requiring discipline. Effective inclusive education demands comprehensive teacher training on autism sensory processing, environmental modifications including noise reduction and visual simplification, and policy-level support for sustained intervention implementation.